2016
DOI: 10.1111/vde.12291
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of medical grade honey in the management of canine otitis externa – a pilot study

Abstract: Medical grade honey was successful in both clinical and laboratory settings, thus demonstrating its potential of becoming an alternative treatment for canine OE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
2
22
0
4
Order By: Relevance
“…This study documents the antibacterial effect of a honey‐based product against S. pseudintermedius, the most common agent causing canine pyoderma . This product also was effective against M. pachydermatis which, along with S. pseudintermedius , frequently causes canine otitis externa . The present work also shows that MSSP and MRSP isolates are equally susceptible to HBO.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This study documents the antibacterial effect of a honey‐based product against S. pseudintermedius, the most common agent causing canine pyoderma . This product also was effective against M. pachydermatis which, along with S. pseudintermedius , frequently causes canine otitis externa . The present work also shows that MSSP and MRSP isolates are equally susceptible to HBO.…”
Section: Discussionmentioning
confidence: 83%
“…L‐Mesitran® Soft, (HBO, Triticum; Maastricht, the Netherlands) is a honey‐based gel composed of 40% medical‐grade honey (HO) which is marketed for the treatment of superficial and acute wounds, superficial and partial thickness burns, chronic wounds, acute and postoperative surgical wounds . Preliminary veterinary clinical data of cases treated with HBO suggests efficacy in the treatment of canine intertrigo and otitis; in vitro documentation of antimicrobial activity is limited …”
Section: Introductionmentioning
confidence: 99%
“…In the veterinary literature, there are several studies investigating the clinical efficacy of antibiotic/antifungal/corticosteroid combination ear products, but none of them have used the validated otitis scoring scale OTI‐3, pruritus VAS scale or the semiquantitative cytology scale described by Budach & Mueller, so that comparisons are not possible . Although some of these studies used an otic cytology scale described by Ginel et al ., we preferred to use the one by Budach & Mueller because it has been validated independently . A pilot study on the use of medical grade honey in 15 dogs affected by acute bacterial and/or yeast otitis reported on the use of the OTI‐3 scale.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study on the use of medical grade honey in 15 dogs affected by acute bacterial and/or yeast otitis reported on the use of the OTI‐3 scale. It reported an initial mean score lower than that of our study (5 versus 6), but a similar improvement curve, confirming that clinical resolution of otitis may occur within 2 weeks of starting treatment …”
Section: Discussionmentioning
confidence: 99%
“…39,40 MGH1 previously has been evaluated in a pilot clinical trial which reported favourable antibacterial potential in canine otitis externa. 41 In addition, MGH1 has been evaluated in vitro reiterating its antifungal and antibacterial properties via a hydrogen peroxide-independent action. 2 In that study, MGH1 was compared to honey, showing that MGH1 had a significantly stronger bactericidal effect than honey alone against S. pseudintermedius isolates (P = 0.003).…”
Section: Discussionmentioning
confidence: 99%